Phase evolution of reactive sputtering synthesized holmium silicate coatings. Issue 1 (25th July 2018) - Hu, Wanpeng; Zhang, Jie; Nian, Hongqiang; Wang, Jingyang
Abstract: Holmium silicates are promising environmental barrier coatings (EBCs) materials for Si‐based non‐oxide ceramics due to their excellent thermal and mechanical properties. In the present work, the phase evolution of holmium silicate coatings synthesized by reactive sputtering was systematically studied. The monosilicate crystallized in an X1‐Ho2 SiO5 phase at 1000°C and transformed to an X2‐Ho2 SiO5 phase at 1200°C. The phase transition is not problematic for the coating process because the X1‐ and X2‐Ho2 SiO5 phases have similar coefficients of thermal expansion (CTEs). For the holmium disilicates, the stoichiometry obviously influenced polymorphic phase evolutions. Relatively Ho2 O3 ‐rich compounds promoted the formation of γ ‐Ho2 Si2 O7 phase at lower temperatures. This study on phase evolution vs temperature and stoichiometry can provide a guideline to optimize the processing and the properties of advanced holmium silicate EBCs.